2021
DOI: 10.1002/hrm.22086
|View full text |Cite
|
Sign up to set email alerts
|

The performance impact of gender diversity in the top management team and board of directors: A multiteam systems approach

Abstract: Given the mixed evidence that having both women and men in the top management team (TMT) or in the board of directors (BOD) has a significant influence on organizational innovation, we resolve this issue by conceptualizing TMT–BOD gender diversity as part of a multiteam system, that has joint effects which impact organizational innovation. Evidence from the study of both Chinese firms and UK firms confirm our conceptualization by showing an interaction effect between TMT gender diversity and BOD gender diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 150 publications
(202 reference statements)
2
39
0
Order By: Relevance
“…In general, whether from the perspective of the corporate strategic decision-making process or the impact on corporate performance, the importance of top management teams in enterprises has been fully affirmed. For instance, a significant body of research explores the influence of age, gender, education level, and other backgrounds of the top management team on executive behaviors and corporate performance [ 14 , 15 , 16 , 17 ]. Furthermore, researchers have added to and revised the upper echelons theory, arguing that the top management team comprises the individuals that are most deeply involved in decision-making and -execution, and have begun to pay more attention to the important role of the top management team in strategic decisions and performance improvements [ 18 , 19 , 20 ].…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, whether from the perspective of the corporate strategic decision-making process or the impact on corporate performance, the importance of top management teams in enterprises has been fully affirmed. For instance, a significant body of research explores the influence of age, gender, education level, and other backgrounds of the top management team on executive behaviors and corporate performance [ 14 , 15 , 16 , 17 ]. Furthermore, researchers have added to and revised the upper echelons theory, arguing that the top management team comprises the individuals that are most deeply involved in decision-making and -execution, and have begun to pay more attention to the important role of the top management team in strategic decisions and performance improvements [ 18 , 19 , 20 ].…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Extant research has extensively studied the superficial factors of managers that are inherent and difficult to change (e.g., gender and age) [ 17 , 38 , 39 ]. Some researchers have suggested that these so-called shallow factors do not cause cognitive conflicts to the same extent that factors such as race do [ 40 ].…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Specifically, we have included four control variables that measure board size, considering the logarithm of the total number of administrators within the board (Board Size). Literature on corporate governance has peacefully noted a greater diversity in larger boards rather than in smallest ones (Safari, 2021;Poletti-Hughes and Briano-Turrent, 2019;Wu et al, 2022) and the likelihood of a more significative diversity in larger boards is easily understood.…”
Section: Control Variablementioning
confidence: 99%
“…Interest in the relationship between team diversity and performance is increasing (Klein et al, 2011;Triana et al, 2021). Many researchers have investigated the effect of team diversity on performance (e.g., Fouskas & D'Isanto, 2021: Wu et al, 2022Zimmerman, 2008;Narayan, Sidh andVolberda, 2021: Triana et al, 2021), and focused on BOD's diversity (e.g., Wu et al, 2022;Veltri, Mazzotta and Rubino, 2021).…”
Section: Board Diversity and Performancementioning
confidence: 99%